2015
DOI: 10.1038/ncomms8176
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activation promotes lipid droplet dispersion on detyrosinated microtubules to increase mitochondrial fatty acid oxidation

Abstract: Lipid droplets (LDs) are intracellular organelles that provide fatty acids (FAs) to cellular processes including synthesis of membranes and production of metabolic energy. While known to move bidirectionally along microtubules (MTs), the role of LD motion and whether it facilitates interaction with other organelles are unclear. Here we show that during nutrient starvation, LDs and mitochondria relocate on detyrosinated MT from the cell centre to adopt a dispersed distribution. In the cell periphery, LD–mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
252
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(263 citation statements)
references
References 55 publications
11
252
0
Order By: Relevance
“…In addition to decreased movement of degradative compartments along the microtubule network, the effects of EtOH are likely to inhibit motility of LDs themselves, organelles also known to exhibit direct links to the microtubule network. In fact, nutrient limitation was shown to promote LD dispersion along detyrosinated microtubules to the cell periphery, promoting interactions between the LD and mitochondria for β‐oxidation 38. Proteins regulating the movement of LDs are only now beginning to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to decreased movement of degradative compartments along the microtubule network, the effects of EtOH are likely to inhibit motility of LDs themselves, organelles also known to exhibit direct links to the microtubule network. In fact, nutrient limitation was shown to promote LD dispersion along detyrosinated microtubules to the cell periphery, promoting interactions between the LD and mitochondria for β‐oxidation 38. Proteins regulating the movement of LDs are only now beginning to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that LU can activate AMPK signalling in differentiated 3T3-L1 adipocytes [24] and HepG2 hepatocytes [23]. In addition, AMPK, as an important nutrient sensor, can promote fatty acid oxidation [37] and energy expenditure [38]. Indeed, in the HFD + LU20 group, dietary LU not only suppressed EAT macrophage polarisation (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…In glioma cells, inhibition of fatty acid oxidation caused significant reduction of NADPH, accumulation of redox oxygen species, and eventually cell death [85]. The involved mechanisms of NADPH production by fatty acid oxidation were later found to be mediated by LKB1-AMPK pathway [86,87]. Lastly, one study demonstrated that leukemia progenitor cells required fatty acid oxidation to maintain stem cell property [88].…”
Section: Lipid Catabolism In Liver Cancer: a Potential Therapeutic Tamentioning
confidence: 99%